Risk Factors of Cervical Cancer Among Women of Reproductive Age at Undata General Hospital Province Central Sulawesi - Prawati, Elis; Nur, Rosmala; Devi, Ratna; Rahman, Abd; Fauzan, Fauzan (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Based on medical record data from Undata Regional General Hospital (RSUD Undata) Palu, 120 cervical cancer (Ca cervix) cases received examination and medical treatment in 2023. This high number indicates that cervical cancer remains a major public health problem in Central Sulawesi. Objective: To analyze the risk factors associated with cervical cancer among women of reproductive age at RSUD Undata, Central Sulawesi Province, in 2024. Method: This quantitative study applied a cross-sectional design and was conducted at RSUD Undata Palu. The sample comprised 69 respondents selected through proportionate stratified random sampling. Data were analyzed using univariate (frequency distribution) and multivariate (multiple linear regression) analyses. Results and Discussion: The analysis revealed that number of marriages (p=0.009), age at first pregnancy (p=0.035), number of children (p=0.000), smoking history (p=0.016), and clinical symptoms (p=0.018) significantly influenced cervical cancer risk. Conversely, age (p=0.727), body weight (p=0.850), ethnicity (p=0.103), menarche (p=0.786), and occupational history (p=0.596) showed no significant association. A greater number of children increased risk due to repeated cervical trauma and hormonal changes during pregnancy that facilitate persistent viral infection. Conclusion: The number of children, clinical symptoms, marital frequency, and smoking history had dominant effects on cervical cancer risk, while age and body weight had no direct influence. The regression model explained 43% of the variation in cervical cancer risk.